In Situ Green Synthesis of Co3O4@ZnO Core-Shell Nanoparticles Using Datura stramonium Leaf Extract: Antibacterial and Antioxidant Studies - Gezahegn Tadesse; H. C. Ananda Murthy; C. R. Ravikumar; T. Naveen Kumar; Lema Teshome; Tegene Desalegn (Bioinorganic Chemistry and Applications)
Investigating and synthesizing potent antibacterial NPs using biological methods is highly preferred, and it involves nontoxic, cost-effective, and environmentally friendly chemicals and methods. Antibiotic drug resistance and oxidative stress have become a serious public health issue worldwide. Hence, the key objective of this study was to biologically synthesize and characterize the potent antibacterial Co3O4@ZnO core-shell nanoparticles for the antibacterial application. The radical scavenging ability of green synthesized Co3O4@ZnO core-shell nanoparticles was also determined. In this study, Co3O4@ZnO core-shell nanoparticles (CZCS NPs) have been synthesized using three different core to shell materials ratios of Co3O4 to ZnO (0.5 : 0.25 CZCS (1), 0.5 : 0.5 CZCS (2), and 0.5 : 0.75 M CZCS (3)) by employing Datura stramonium leaf extract. The polycrystalline nature of Co3O4@ZnO core-shell nanoparticles was investigated using the XRD and SAED characterization techniques. The investigated nanostructure of Co3O4@ZnO core-shell nanoparticles appeared with Co3O4 as the core and ZnO as an outer shell. Additionally, a variety of physicochemical properties of the nanoparticles were determined using various characterization techniques. The average crystallite sizes of CZCS (1), CZCS (2), and CZCS (3) were found to be 24±1.4, 22±1.5, and 25±1.5 nm, respectively. The band gap energy values for CZCS (1), CZCS (2), and CZCS (3) determined from the UV-DRS data were found to be 2.75, 2.76, and 2.73 eV, respectively. The high inhibition activities against S. aureus, S. pyogenes, E. coli, and P. aeruginosa bacterial strains were obtained for the small size CZCS (2) nanoparticles at the concentration of 100 mg/mL with 22 ± 0.34, 19 ± 0.32, 18 ± 0.45, and 17 ± 0.32 mm values, respectively. The high inhibition performance of CZCS (2) nanoparticles against Gram-positive and Gram-negative bacteria which is even above the control drug ampicillin is because of its small size and synergistic effect. The percentage scavenging activity of Co3O4@ZnO core-shell nanoparticles was also studied and CZCS (2) nanoparticles showed a good scavenging capacity (86.87%) at 500 μg/mL with IC50 of 209.26 μg/mL.